Gender, Ageing and Extended Working Life 2017
DOI: 10.1332/policypress/9781447325116.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

Sweden: an extended working life policy that overlooks gender considerations

Abstract: The Swedish government policy on extended working life has since its introduction in the mid-1990s aimed to lower the costs of the public pension system and to reduce the financial burden for workers. By focusing on an idealised category of those who are "willing and able to work longer", the policy has neglected the obstacles faced by those with physically demanding jobs or with a big responsibility to care for a close relative. This mainly affects women and upholds a neoliberal view of older people. By only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…How likely is it that a person in paid work at age 55 will remain in work and experience better working conditions in their late sixties? There may be substantial differences in relation to societal context and individual characteristics, be they ascribed characteristics such as race and gender or earlier circumstances and events (Krekula et al, 2017; McAllister et al, 2019). Future research could incorporate trajectories involving withdrawal from the labour market while measuring temporal variations in working conditions.…”
Section: Discussionmentioning
confidence: 99%
“…How likely is it that a person in paid work at age 55 will remain in work and experience better working conditions in their late sixties? There may be substantial differences in relation to societal context and individual characteristics, be they ascribed characteristics such as race and gender or earlier circumstances and events (Krekula et al, 2017; McAllister et al, 2019). Future research could incorporate trajectories involving withdrawal from the labour market while measuring temporal variations in working conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers' experience of stressful conditions is multifaceted. First, stresses are found in organizational structures with reduced resources, demanding psychosocial work environment bringing stress and pressure as a consequence (Krekula, Engström, & Alvinius, 2017), shifting job satisfaction, but also antagonistic aspects such as bullying and abuse. Second, the working environment for teachers seems to be one of the most stressful of all occupational groups (Kjellström, Almquist, & Modin, 2016), which is the result of the 1990s school reforms (SOU, 2014:5) and resource reductions in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the three empirical indicators used by Möhring, we included an additional criterion, based on broad EWL policy orientations adopted in the mid-2000s in different national contexts (Buchholz et al, 2006;Ní Léime et al, 2017, 2020. Previous research has identified two main policy responses to population ageing: 'employment exit' policies, which encourage the early retirement of older workers, and 'employment maintenance' policies, which provide opportunities for extending working lives (Buchholz et al, 2006;König and Schilling, 2016).…”
Section: Gendered Lifecourse Regimes and Employment Policiesmentioning
confidence: 99%